2017
DOI: 10.1017/dmp.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Zika-Virus-Related Photo Sharing on Pinterest and Instagram

Abstract: Pinterest and Instagram are similar platforms for Zika virus prevention communication. (Disaster Med Public Health Preparedness. 2017;11:656-659).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 5 publications
2
24
0
Order By: Relevance
“…Seltzer et al [ 17 ] analyzed the Instagram photos with the #zika tag and found that they were primarily related to the prevention and transmission of the disease. Fung et al [ 18 ] also analyzed the content of Zika-related photos and found that its prevention, its effects on pregnancy, and the deaths associated with it were major categories. Instagram posts with the #melanomasucks tag were analyzed by Cho et al [ 19 ], with the most frequent content being controlling melanoma and the effects of having melanoma.…”
Section: Related Workmentioning
confidence: 99%
“…Seltzer et al [ 17 ] analyzed the Instagram photos with the #zika tag and found that they were primarily related to the prevention and transmission of the disease. Fung et al [ 18 ] also analyzed the content of Zika-related photos and found that its prevention, its effects on pregnancy, and the deaths associated with it were major categories. Instagram posts with the #melanomasucks tag were analyzed by Cho et al [ 19 ], with the most frequent content being controlling melanoma and the effects of having melanoma.…”
Section: Related Workmentioning
confidence: 99%
“…Key topics included pregnancy and abortion. Concerning Instagram imagery, prior analyses focused on information dissemination [31] and comparison between Pinterest and Instagram for communicating about Zika [17].…”
Section: Related Workmentioning
confidence: 99%
“…Specifically, in that study it was investigated whether the percentage of Zika‐virus‐related photos with Spanish or Portuguese texts embedded therein was higher for Instagram than for Pinterest and whether the contents of Zika‐virus‐related photos shared on Pinterest were different from those shared on Instagram. Both photo‐sharing platforms were similar for Zika virus prevention communication .…”
Section: Zika Virus and Health Communication In The 21st Centurymentioning
confidence: 99%